Transaksi valuta asing sarf dalam konsepsi fikih mu’amalah - Suryani Suryani (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
Buying and selling foreign currencies (as-Sarf) basically arises because of the need for conversion of one currency to another currency in international trade traffic that will encourage the supply and demand for foreign exchange, which in turn will bring up the sale and purchase of foreign currency in the foreignexchange market. The practice of buying and selling foreign currency according to fiqh mu’amalah is permitted if it is done by an agreement between the two sides and in cash (spot) and it could not be included the addition of a similar item like gold with gold or silver with silver.